MODULAÇÕES MORFOFISIOLÓGICAS E TOLERÂNCIA AO CÁDMIO (Cd) EM Alternanthera tenella Colla (AMARANTHACEAE) DURANTE O CULTIVO IN VITRO E O POTENCIAL DO ZINCO (Zn) COMO MITIGADOR DE ESTRESSE INDUZIDO PELO Cd - Clairvil, Evens (2021)
The excess of trace elements in the environment is toxic to living beings and shows the need for stress relief elements in the habitat. Cadmium (Cd) has no biological role and is considered toxic to plants. Zinc (Zn), through its potential to detoxify trace elements and increase photosynthetic activity, has been cited as a mitigation to the harmful effects induced by Cd. In this context, it is proposed to evaluate the morphophysiological modulations and tolerance of plants of the species Alternanthera tenella to Cd under controlled conditions, in addition to verifying the potential of Zn as a mitigator of stress induced by Cd. Two experiments were carried out that will be presented and described, in chapters I and II, respectively, of this dissertation. In the first experiment, nodal segments of A. tenella were grown in flasks containing semi-solid MS medium supplemented with 0, 50, 100 and 150 μM of Cd. After 30 days of cultivation, the total fresh and dry weight of the plants were determined , in addition to the content of photosynthetic pigments, chlorophyll a fluorescence and tolerance index (IT). This study showed that Cd reduced the biomass and the content of photosynthetic pigments, induced photochemical dysfunctions with decreases in qL, qN and qP and increased WL, WK and ΦNO (indicative of photodanes). In addition, the plants had a low IT level (≥21.7) in the analyzed concentration range. A. tenella does not tolerate concentrations greater than 100 μM of Cd and showed a level of physiological responses clearly dependent on the concentrations of this metal. In the second experiment, nodal segments of A. tenella grown in Zn-modified MS medium (without Zn) were grown in flasks containing semi-solid MS medium supplemented with three levels of Cd (0, 75 or 150 μM) and Zn (0, 750 or 1500 μM). Again, after 30 days of cultivation, the anatomy of the leaves and stem, the total dry weight of the plants, in addition to the chlorophyll a fluorescence and tolerance index (TI) were determined. The anatomical structures (stem/leaf) of the plants showed a reduction due to both trace elements. With exposure only to Cd, the plants showed physiological disturbances, compromising their growth. Supplementation of Zn in the medium has a positive effect on the physiological performance of plants, in concentrations ≤ 750 μM it can partially alleviate the deleterious effects of Cd. Plants cultivated with Zn and Cd exhibited an intermediate IT (≈ 40.68), proving the potential of Zn as a stress reliever induced by Cd in plants. Thus, from an ecotoxicological point of view, the excess of both trace elements (Cd and Zn) represents toxicity to the species studied.